2018
DOI: 10.1534/genetics.117.300208
|View full text |Cite
|
Sign up to set email alerts
|

Protecting and Diversifying the Germline

Abstract: Gametogenesis represents the most dramatic cellular differentiation pathways in both female and male flies. At the genome level, meiosis ensures that diploid germ cells become haploid gametes. At the epigenome level, extensive changes are required to turn on and shut off gene expression in a precise spatiotemporally controlled manner. Research applying conventional molecular genetics and cell biology, in combination with rapidly advancing genomic tools have helped us to investigate (1) how germ cells maintain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 432 publications
(595 reference statements)
0
34
0
Order By: Relevance
“…In the anterior half of the germarium, cysts arise from the mitotic expansion of GSCs and their differentiating daughters (Figures 2D, 3). GSCs divide mitotically with asymmetric division, giving rise to two cells of unequal fates: a new stem cell and a cystoblast destined for differentiation (Schüpbach et al, 1978;Wieschaus and Szabad, 1979;Lin and Spradling, 1993;reviewed in: Xie, 2013;Gleason et al, 2018;Drummond-Barbosa, 2019;Kahney et al, 2019). The cystoblast undergoes exactly four rounds of mitotic division with incomplete cytokinesis, creating interconnected 2, 4, 8, and 16 cell cysts (King, 1970;Spradling, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In the anterior half of the germarium, cysts arise from the mitotic expansion of GSCs and their differentiating daughters (Figures 2D, 3). GSCs divide mitotically with asymmetric division, giving rise to two cells of unequal fates: a new stem cell and a cystoblast destined for differentiation (Schüpbach et al, 1978;Wieschaus and Szabad, 1979;Lin and Spradling, 1993;reviewed in: Xie, 2013;Gleason et al, 2018;Drummond-Barbosa, 2019;Kahney et al, 2019). The cystoblast undergoes exactly four rounds of mitotic division with incomplete cytokinesis, creating interconnected 2, 4, 8, and 16 cell cysts (King, 1970;Spradling, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila melanogaster is an ideal model organism for the detailed study of oogenesis. Drosophila females have one pair of ovaries that consist of 18-20 ovarioles (reviewed in [1][2][3]). In germarium-a structure at the anterior tip of the ovariole-two or three germline stem cells (GSCs) are maintained in the undifferentiated status in a niche environment.…”
Section: Introductionmentioning
confidence: 99%
“…The RNAi system of the insect last common ancestor diversified and expanded through time across the different insect lineages (Dowling et al., ). Although the canonical functions of piRNAs are associated with genome protection from transposon activity during embryogenesis, evidences of additional roles (like regulation of gene expression) are growing (Gebert, Ketting, Zischler, & Rosenkranz, ; Gleason et al., ; Le Thomas et al., ; Lewis et al., ; Peng & Lin, ; Pritykin, Brito, Schupbach, Singh, & Pane, ; Sarkar, Volff, & Vaury, ). As the taxonomic spectrum of studied species broadens, the complexity of the piRNA system appears to expand.…”
Section: Discussionmentioning
confidence: 99%
“…The piRNA transcription does not seem to occur through canonical promoters. It has been proposed that the Rhino‐Deadlock‐Cutoff (RDC) complex would participate in regulating the transcription of piRNA clusters in germ cells, inhibiting the transcription of adjacent genes in the cluster or allowing the functionality of noncanonical promoters (Gleason, Anand, Kai, & Chen, ). Moreover, the localization of some piRNA clusters in heterochromatic regions led to the study of them in relation to histone modifications, which has revealed an important role of H3K9me3 on cluster transcription (Mohn, Sienski, Handler, & Brennecke, ; Molla‐Herman, Vallés, Ganem‐Elbaz, Antoniewski, & Huynh, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation